If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying f(x) = (3x + -4)(-6x + 5) Multiply f * x fx = (3x + -4)(-6x + 5) Reorder the terms: fx = (-4 + 3x)(-6x + 5) Reorder the terms: fx = (-4 + 3x)(5 + -6x) Multiply (-4 + 3x) * (5 + -6x) fx = (-4(5 + -6x) + 3x * (5 + -6x)) fx = ((5 * -4 + -6x * -4) + 3x * (5 + -6x)) fx = ((-20 + 24x) + 3x * (5 + -6x)) fx = (-20 + 24x + (5 * 3x + -6x * 3x)) fx = (-20 + 24x + (15x + -18x2)) Combine like terms: 24x + 15x = 39x fx = (-20 + 39x + -18x2) Solving fx = -20 + 39x + -18x2 Solving for variable 'f'. Move all terms containing f to the left, all other terms to the right. Divide each side by 'x'. f = -20x-1 + 39 + -18x Simplifying f = -20x-1 + 39 + -18x Reorder the terms: f = 39 + -20x-1 + -18x
| 25c=.7 | | 4x^2=x-3 | | m^2=11(m-2) | | 50+3x=77 | | 4x^2-2.8x-5.7=0 | | -y^2=6y-1 | | -y^2=6y-2 | | 7.5-x=26.8 | | 2x+20=25x+35 | | (3x/x-5)-(2/x^2-25 | | 3m/2-1=8 | | -7x^2+1=7y | | 3(j+7)=7jsquared | | X=tan3y/6 | | 18/16=n/24 | | 6x+2=4x+17-3x | | x+4(-1)=0 | | 4(x-3)-5(x-2)=4(4-x) | | 4b+2-b=b+12 | | 3(-4y)-4y=16 | | 9g^2-35=14 | | h+24=g | | 7x+8=7(x+9) | | 2x-12-5x=7x-72 | | 102+7x-13+6x+8x-2=360 | | 5x(x^2+7)= | | 11(x+4)= | | 6x=-2x+12 | | 70=16t^2+128t | | 0.40x+0.90(20)=0.20(48) | | x=(y-100)/2.8 | | 20(y+6)+5y=20 |